ENGAGING THE TRADE COMMUNITY: BUILDING TRUST AND TRANSPARENCY IN CUSTOMS OPERATIONS - Rosli, Farah Nor Aishah (Jurnal BPPK: Badan Pendidikan dan Pelatihan Keuangan, 2024)
This paper explores the critical role of trust and transparency in enhancing compliance and cooperation within customs operations. Utilizing a conceptual framework for institutional trust, the study investigates how customs authorities can build trust through competency, integrity and fairness. Additionally, the paper examines the impact of both trust and transparency on compliance and cooperation among stakeholders, drawing on existing literature that supports these relationships. Through a combination of literature review and case studies, this research aims to identify key factors that influence trust and transparency in customs operations and propose strategies for customs administrations to foster a more collaborative and compliance trade environment The findings will provide valuable insights for policymakers and customs authorities in implementing practices that enhance trust and transparency, ultimately leading to improved compliance and efficiency In customs operations.